RELATIONSHIP BETWEEN METALLOPROTEINASE AND TIMP1 EXPRESSION AND INTENSITY OF CERVICAL INFLAMMATORY REACTION IN WOMEN OF DIFFERENT AGE GROUPS WITH CERVICAL INTRAEPITHELIAL NEOPLASIA AND MICROINVASIVE CARCINOMA - M. S. Seliakova; T. A. Ageeva; S. V. Savchenko (Сибирский онкологический журнал)
Objective: to study the relationship between metalloproteinases and expression TIMP1 expression and intensity of inflammatory response in the cervical stroma of women with cervical intraepithelial neoplasia and microinvasive carcinoma. Material and methods. Morphological, morphometric and immunohistochemical examination of cervical biopsies in patients with cervical epithelial neoplasia (cINI–III) and microinvasive carcinoma was carried out. all patients were divided into two age groups: group 1 consisted of 95 patients of early reproductive age ranged from 18 to 35 years (mean age 28.5 ± 0.58 years) and group 2 consisted of 85 perimenopausal and menopausal patients aged 49 to 65 (mean age 55.4 ± 0.98 years). Results. In women of both age groups, the density of inflammatory cell infiltrate was shown to increase, being significantly higher in women of group 1 than in women of group 2. the increase in the expression level of metalloproteinases-2, -3, -7, and -9 with dysplasia progression was observed in women of both age groups, being also higher in group 1 women. the tIMP1 expression level was higher in group 2 women and increased with disease progression. Conclusion. In young women, pronounced and active inflammation in the cervical stroma contributes to a high potential for metalloproteinase synthesis. a higher level of tIMP1 expression in perimenopausal and menopausal women may be one of the factors contributing to a decrease in the metalloproteinase synthesis in these women.